From Reactive to Proactive: A QIP for Improving Physical Health Monitoring and Management for Children and Young People with Eating Disorders - Sanaa Moledina; Bronwyne Stott (BJPsych Open)
Aims: Effective monitoring of children and young people (CYP) with eating disorders (ED) is vital to prevent complications such as malnutrition, electrolyte imbalances, and refeeding syndrome. Assessments at the Northamptonshire Healthcare NHS Foundation Trust Children and Young People Community Eating Disorder Service (NHFT CYPCEDS) & Leicestershire CAMHS Eating Disorder Team (LPT CAMHS EDT) revealed poor coordination between primary care, the clinics, and paediatric hospitals, coupled with limited staff knowledge of physical complications in ED and their management. This contributed to delayed and substandard referrals, high-acuity cases, and increased paediatric admissions. Reliance on GPs, owing to capacity issues, resulted in inconsistent and subpar physical monitoring. Therefore, we aimed to improve physical health monitoring and management for CYP with known ED in Northamptonshire and Leicestershire.